Oral healthcare beliefs among home care services personnel; a cross-sectional study in south-eastern Norway - Hero Ibrahim Hassan; V. E. Ansteinsson; E. T. Dalbak; R. Skudutyte-Rysstad; R. Hellesø; I. Mdala; E. A. Sz. Hovden (BMC, 2024)
Abstract Background There is little knowledge about home care services personnel competencies and beliefs concerning oral healthcare for home-dwelling, dependent older adults. This study aims to map oral healthcare beliefs among home care services personnel, and have the following question: How do the education level, years of work experience and training in oral health have impact on home care services personnel oral healthcare beliefs? Methods A cross-sectional study among home care services personnel working with older people receiving home care services was conducted across four municipalities in south-eastern Norway. The questionnaire consisted of background information (gender, education level, years of work experience, training in oral healthcare, employment status) and the nursing Dental Coping Beliefs scale. Ethics approval for this study was obtained from the Norwegian Centre for Research Data. Results Two hundred and sixty-two homecare services personnel responded to the questionnaire, 16.5% males and 83.5% females; 40.5% had had training in oral healthcare. Home care services personnel believed that gum diseases and cavities can be prevented by dental flossing (61.4%) and toothbrushing (98.4%). 59% disagreed that preventing sickness and medicines from destroying teeth is impossible. However, the majority of the home care services personnel were uncertain about how oral mucosal disorders can be treated. Having more than three years of higher education was positively associated with being in higher quartiles of oral healthcare beliefs, and external locus of control, and having training in oral healthcare was positively associated with being in the lower quartiles of internal locus of control and self-efficacy dimensions. Males were more likely to be in the lower quartile of oral healthcare beliefs, which wasn't positive. Conclusion In the population studied, the home care services personnel beliefs about oral healthcare improved with an increasing level of education and having had training in oral healthcare. This suggests that home care services personnel need more education and training in oral healthcare.